Danger on midnight river - Paulsen, Gary.; Paulsen, Gary.; Paulsen, Gary.; Paulsen, Gary. (New York : Yearling, 1995)
A compilation of three titles from Gary Paulsen's World of adventure series.
Escape from Fire Mountain -- Hook 'em, Snotty! -- Danger on Midnight River.
"A Yearling book."
Keywords: Forest fires -- Juvenile fiction; Ranch life -- Juvenile fiction; Wilderness survival -- Juvenile fiction; Adventure stories; Adventure and adventurers -- Fiction; Forest fires -- Fiction; Ranch life -- Fiction; Wilderness survival -- Fiction